2019
DOI: 10.31925/farmacia.2019.3.11
|View full text |Cite
|
Sign up to set email alerts
|

A New Non-Extractive Ion-Pair Spectrophotometric Method for the Assay of Albendazole

Abstract: The paper presents a new non-extractive spectrophotometric method for the assay of albendazole (ABZ) as ion pair with Congo red (CR). A soluble and stable ion pair (ABZ-CR) with an absorption maximum at 294 nm was obtained using a 2•10 -8 M CR concentration and Britton Robinson (BR) buffer with pH = 2.5. The method is linear in the range 2.5 -4.7 µg/mL, with limits of detection and quantification of 0.09 µg/mL and 0.28 µg/mL, respectively. The proposed method was applied to the assay of ABZ in bulk pharmaceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The existing J 2023, 6 249 spectrophotometric methods for the determination of nimesulide are summarized in Table 1 and those for meloxicam in Table 2. Water/chloroform Hexadecyl-trimethylammonium bromide 404 6-20 1 0.7 [13] Water/chloroform Bromocresol green 412 2-18 5 0.6 [14] Water/chloroform Bromocresol purple 410 2-16 4 0.5 [14] Water/chloroform Bromothymol blue 407 2-18 3 0.5 [14] Water/chloroform Brilliant blue G 502 2-18 5 0.5 [14] Water/chloroform Methyl orange 482 2-14 3 0.7 [14] Water p-N,N-dimethyl phenylene diamine dihydrochloride, chloramine-T 540 10-50 0.8 0.6 [15] Water p-N,N-dimethyl phenylene diamine dihydrochloride, These methods were checked for rapidness, simplicity and usage of the reagents common for pharmaceutical laboratory; it was found that the simplest methods (that allowed the determination of nimesulide and meloxicam content directly in the aqueous solutions without lengthy phase separation steps and sample or reagent preparation and that used only very common reagents available in any pharmaceutical laboratory) were based on the formation of the colored deprotonated forms of nimesulide and meloxicam in alkaline environments. Both these active pharmaceutical ingredients exhibited an acid-base behavior and, in the presence of NaOH, formed the intensively colored yellow solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The existing J 2023, 6 249 spectrophotometric methods for the determination of nimesulide are summarized in Table 1 and those for meloxicam in Table 2. Water/chloroform Hexadecyl-trimethylammonium bromide 404 6-20 1 0.7 [13] Water/chloroform Bromocresol green 412 2-18 5 0.6 [14] Water/chloroform Bromocresol purple 410 2-16 4 0.5 [14] Water/chloroform Bromothymol blue 407 2-18 3 0.5 [14] Water/chloroform Brilliant blue G 502 2-18 5 0.5 [14] Water/chloroform Methyl orange 482 2-14 3 0.7 [14] Water p-N,N-dimethyl phenylene diamine dihydrochloride, chloramine-T 540 10-50 0.8 0.6 [15] Water p-N,N-dimethyl phenylene diamine dihydrochloride, These methods were checked for rapidness, simplicity and usage of the reagents common for pharmaceutical laboratory; it was found that the simplest methods (that allowed the determination of nimesulide and meloxicam content directly in the aqueous solutions without lengthy phase separation steps and sample or reagent preparation and that used only very common reagents available in any pharmaceutical laboratory) were based on the formation of the colored deprotonated forms of nimesulide and meloxicam in alkaline environments. Both these active pharmaceutical ingredients exhibited an acid-base behavior and, in the presence of NaOH, formed the intensively colored yellow solutions.…”
Section: Introductionmentioning
confidence: 99%